CLINICO-ETIOLOGICAL PROFILE OF CONVULSIONS IN CHILDREN AMONG ONE MONTH TO 18 YEARS OF AGE AT TERTIARY CARE CENTER JAIPUR, RAJASTHAN - VERMA, VARUN; AGRAWAL, VIJAY; GARG, VIJENDRA; BANSAL, SHARAD; SHARMA, JN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this were to study the clinico-etiological profile of convulsions in children aged 1 month to 18 years, to analyze the types of seizures and their categorization according to age, cause, type, and symptoms and signs associated with convulsion. Methods: This was a cross-sectional hospital-based observational study conducted in the Department of Pediatrics, SPMCHI hospital, SMS Medical College, Jaipur, India for a period of January 2019–November 2020 on subjects of age group from 1 month to 18 years. All participants were thoroughly examined by complete history taking and investigated with complete blood counts, metabolic screening, lumbar puncture and CSF analysis, electroencephalography, CT scan, and MRI as and when required. Results: Occurrence of convulsions was more in male gender (60.5%), with highest 226 (56.5%) in the age group between 1 month and <5 years, whereas lowest was found between age 10 and 18 years 59 (14.9%). Conclusion: The incidence of convulsions was highest in the younger age group, with generalized tonic-clonic seizure being the most common type. Febrile convulsion was the most common etiology. About one-third had abnormal MRI finding, whereas more than two-third of performed patients had abnormal EEG finding.